A Study of Digital Image Segmentation Techniques (International Journal of Engineering and Computer Science, 2018)
In the 21st century, the internet revolution has brought about an explosion of information in the form of documents and web pages. Today, more and more focus is being given to visual representation of data. Digital Image Processing has thus emerged as one of the most researched fields in the computer domain. Image segmentation is important part in many signal processing technique and its applications. It is the process of partitioning a digital image and dividing it into meaningful structures known as segments (sets of pixels, also known as superpixels). It is often an essential step in image analysis, object representation, visualization, and many other image processing tasks. Image segmentation is a great challenge in the field of computer vision. The aim of this paper is to give an overview of image segmentation and the techniques for the same.